Perceived impact of the COVID-19 pandemic on postgraduate residents - Ajay Solanki; Hrishikesh Solunke; T S Sathyanarayana Rao; M Kishor (Annals of Indian Psychiatry, 2023)
Introduction: COVID-19 has led to an increase in burden on health-care workers. Postgraduate residents are at the forefront of the pandemic. Understanding its impact and the perspectives of postgraduate residents could provide better solutions to their problems. Objectives: 1. To assess the psychological impact of the COVID-19 pandemic on postgraduate doctors. 2. To assess the perception of postgraduate doctors regarding the medical profession and its association to the psychological impact of the COVID-19 pandemic. Methodology: This cross-sectional study recruited 65 postgraduate medical resident doctors working in teaching hospitals involved in the care of COVID-19 patients. They were requested to complete the questionnaire consisting of qualitative as well as quantitative questions. For an objective assessment of anxiety, the Generalized Anxiety Disorder-7 (GAD-7) scale was used. Relevant statistical methods were employed and statistical analysis was done using IBM SPSS software version 20.0. Results: The qualitative data showed themes of concern regarding social awareness about COVID-19 (hygiene, masks, and social distancing), working conditions of doctors, and increased stress and burnout. 47.54% (n = 29) of respondents said that they would reconsider their profession/specialty, out of which 21 said that they would switch to another profession. The resident doctors who would reconsider their choice of profession/specialty had significantly higher (P < 0.05) scores for anxiety (GAD-7). Conclusion: Owing to the significant association between anxiety and desire to change their profession altogether, greater psychological support for doctors appears to be a pressing need. It is important that the concerns of the postgraduate residents are addressed promptly and holistically.